IMPLEMENTASI ALGORITMA APRIORI UNTUK MENENTUKAN POLA DATA PENYAKIT PADA ANAK USIA DINI (STUDI KASUS: RS. ESTOMIHI) - Purba, Citra Verawati; Buulolo, Efori (STMIK Budi Darma, 2020)
Hospital is a place to treat patients with different types of diseases, and hospitals are also one of the health services that are medical, healing and recovery for patients. Many people who want to seek treatment at the hospital both parents and including early childhood. Based on this, researchers are interested in looking for patterns from large-scale data and associating data with one another using the Apriori algorithm. Thus, the diseases suffered by early childhood can be classified based on the medical record data, so that the pattern of early childhood disease can be known. The information produced can be used by the Hospital and the doctors on duty at the hospital to take the necessary actions in order to prevent the spread of a disease and also reduce the risk of death of patients suffering from disease